2016
DOI: 10.1002/elps.201600149
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective determination of cathinone derivatives in human hair by capillary electrophoresis combined in‐line with solid‐phase extraction

Abstract: A suitable method has been developed and validated for the chiral separation and determination of R,S-mephedrone and one of its metabolites, R,S-4-methylephedrine, and R,S-methylenedioxypyrovalerone (R,S-MDPV) in human hair samples by the in-line coupling between SPE and CD-assisted CE with a previous sample pretreatment procedure based on pressurized liquid extraction. Optimum separation was achieved on a fused silica-capillary of 50 μm id and 80 cm total length using 12 mg/mL β-CD in an aqueous solution of 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 32 publications
0
44
0
Order By: Relevance
“…Enantiomers of all three were not well separated by native β-CD but the resolutions were improved using S-β-CD (R s = 1.3, 1.7 and 6.4 respectively). In contrast, a recent study showed that S-β-CD did not work as expected but native β-CD enabled the chiral separation of 4-methylmethcathinone (4-MMC) and 3,4-methylenedioxypyrovalerone (3,4-MDPV) [29], possibly because of the different experimental conditions applied such as the identity and pH value of buffer solution.…”
Section: Capillary Electrophoresis (Ce)mentioning
confidence: 85%
“…Enantiomers of all three were not well separated by native β-CD but the resolutions were improved using S-β-CD (R s = 1.3, 1.7 and 6.4 respectively). In contrast, a recent study showed that S-β-CD did not work as expected but native β-CD enabled the chiral separation of 4-methylmethcathinone (4-MMC) and 3,4-methylenedioxypyrovalerone (3,4-MDPV) [29], possibly because of the different experimental conditions applied such as the identity and pH value of buffer solution.…”
Section: Capillary Electrophoresis (Ce)mentioning
confidence: 85%
“…While our method also does not attain the level of chiral resolution seen in the similar Silva et al 14 described method, it did achieve a 400-fold improvement in the LLOQ compared to the quantitative Baciu method. 15 …”
Section: Discussionmentioning
confidence: 99%
“…Baciu et al report a chiral quantitative capillary electrophoresis method for the determination of MDPV enantiomers in hair, with a lower limit of quantitation (LLOQ) of 0.4 ng/mg which equates to about 400 ng/ml. 15 Considered together, none of these chiral selective methods were designed for quantitation of the low ng/ml concentrations of MDPV enantiomers expected in rodent pharmacokinetic studies with small serum or plasma sample volumes (20 – 50 µl).…”
Section: Introductionmentioning
confidence: 99%
“…Satisfactory recoveries ranging from 81 to 95% were obtained for all analytes. The same group constructed a similar SPE column for the preconcentration of racemic mephedrone and its metabolites, whereby LOD as low as 0.02 ng/mg was achieved for one of the enantiomer . The similarity from both works was that the authors managed to minimize current instability and breakdown during the CE separation, a common issue when conducting in‐line SPE using discontinuous packed bed in the same capillary with CE separation.…”
Section: Extractionmentioning
confidence: 99%
“…Schematic illustration of the different steps of cis‐diols compounds analysis: preconcentration and purification on the integrated μBAMC unit, acidic elution, CZE separation and UV detection. Reprinted from with permission.…”
Section: Extractionmentioning
confidence: 99%